Artificial intelligence, ethics, and diffused pivotality - Victor Klockmann; Alicia von Schenk; Marie-Claire Villeval (Leibniz Institute for Financial Research SAFE, 2022)
With Big Data, decisions made by machine learning algorithms depend on training data generated by many individuals. In an experiment, we identify the effect of varying individual responsibility for the moral choices of an artificially intelligent algorithm. Across treatments, we manipulated the sources of training data and thus the impact of each individual's decisions on the algorithm. Diffusing such individual pivotality for algorithmic choices increased the share of selfish decisions and weakened revealed prosocial preferences. This does not result from a change in the structure of incentives. Rather, our results show that Big Data offers an excuse for selfish behavior through lower responsibility for one's and others' fate.
Keywords: C49; C91; D10; D63; D64; O33; 330; Artificial Intelligence; Big Data; Pivotality; Ethics; Experiment